Equisetin Restores Colistin Sensitivity against Multi-Drug Resistant Gram-Negative Bacteria - Qi Zhang; Shang Chen; Xiaojia Liu; Wenhan Lin; Kui Zhu (Antibiotics, 2021)
The overuse of antibiotics and the scarcity of new drugs have led to a serious antimicrobial resistance crisis, especially for multi-drug resistant (MDR) Gram-negative bacteria. In the present study, we investigated the antimicrobial activity of a marine antibiotic equisetin in combination with colistin against Gram-negative bacteria and explored the mechanisms of synergistic activity. We tested the synergistic effect of equisetin in combination with colistin on 23 clinical mcr-1 positive isolates and found that 4 µg/mL equisetin combined with 1 µg/mL colistin showed 100% inhibition. Consistently, equisetin restored the sensitivity of 10 species of mcr-1 positive Gram-negative bacteria to colistin. The combination of equisetin and colistin quickly killed 99.9% bacteria in one hour in time-kill assays. We found that colistin promoted intracellular accumulation of equisetin in colistin-resistant E. coli based on LC-MS/MS analysis. Interestingly, equisetin boosted ROS accumulation in E. coli in the presence of colistin. Moreover, we found that equisetin and colistin lost the synergistic effect in two LPS-deficient A. baumannii strains. These findings suggest that colistin destroys the hydrophobic barrier of Gram-negative bacteria, facilitating equisetin to enter the cell and exert its antibacterial effect. Lastly, equisetin restored the activity of colistin in a G. mellonella larvae infection model. Collectively, these results reveal that equisetin can potentiate colistin activity against MDR Gram-negative bacteria including colistin-resistant strains, providing an alternative approach to address Gram-negative pathogens associated with infections in clinics.